Encyclopedia of human geography - Warf, Barney 1956- (Gale virtual reference library, 2006)
Offers a comprehensive overview of the major ideas, concepts, terms, and approaches of human geography. This multidisciplinary volume provides cross-cultural coverage of the field as it is understood in the contemporary world and takes into account the enormous conceptual changes that have evolved since the 1970s. More than 300 entries were written by an international team of leading authorities in the field.